CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

Which of the following is correct:


  1. cos(A – B) = cosA cosB + sinA sinB

  2. cos(A + B) = cosA cosB + sinA sinB

  3. cos(A + B) = cosA + cosB

  4. cos(A – B) = cosA – cosB


Solution

The correct option is A

cos(A – B) = cosA cosB + sinA sinB


cos(x + y) = cosx cosy – sinx siny

Replacing y by –y in the above identity, we get

cos (x – y) = cosx cosy + sinx siny

flag
 Suggest corrections
thumbs-up
 
0 Upvotes


Similar questions
View More...



footer-image